Dampak Komunikasi Terhadap Psikologi - Maulana Yusuf; Leo Feni Agustina; Deden Deden; Noerma Kurnia Fajarwati (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2024)
In the current digital era, communication has become an integral element in daily life, with significant impacts on individual psychology. This research aims to examine the impact of communication on individual psychology, particularly in the context of information technology and social media. The research method employed is a literature analysis involving a study of various articles, books, and scholarly journals related to the topic. The analysis results indicate that communication through information technology and social media has a complex influence on individual psychology. It is found that the use of social media can affect self-esteem, self-image, anxiety, and emotional well-being. Additionally, there are also negative impacts such as addiction, depression, and sleep disturbances associated with intensive communication patterns via social media. However, the research also highlights the positive potential of digital communication in facilitating social support, expanding social networks, and enhancing individual psychological well-being.